Psychosocial Mediators of Two Community-Based Physical Activity Programs. Issue 1 (18th December 2013) - Becofsky, Katie; Baruth, Meghan; Wilcox, Sara
Abstract: Background: Previous findings are inconclusive regarding the mediators of physical activity behavior change. Purpose: To test self-efficacy and social support as mediators of Active Choices, a telephone-delivered physical activity intervention, and Active Living Every Day, a group-based physical activity intervention, implemented with midlife and older adults in community settings. Methods: MacKinnon's product of coefficients was used to examine social support and self-efficacy as mediators of change in physical activity. The proportion of the total effect mediated was calculated. Each model controlled for age, gender, race (white vs. non-white), body mass index (BMI), and education (high school graduate or less vs. at least some college). Results: Increases in self-efficacy mediated increases in physical activity among Active Choices ( n  = 709) and Active Living Every Day ( n  = 849) participants. For Active Living Every Day, increases in social support also mediated increases in physical activity in single mediator models. Conclusions: Increasing self-efficacy and social support may help increase physical activity levels in older adults.